BmSPP is a virus resistance gene in Bombyx mori - Feng, Yu-ting; Yang, Chun-yan; Wu, Lin; Wang, Yuan-cheng; Shen, Guan-wang; Lin, Ping (Frontiers in Immunology, 2024)
Signal peptide peptidase (SPP) is an intramembrane protease involved in a variety of biological processes, it participates in the processing of signal peptides after the release of the nascent protein to regulate the endoplasmic reticulum associated degradation (ERAD) pathway, binds misfolded membrane proteins, and aids in their clearance process. Additionally, it regulates normal immune surveillance and assists in the processing of viral proteins. Although SPP is essential for many viral infections, its role in silkworms remains unclear. Here, we examined the gene expression patterns of BmSPP and observed a decreased in its expression during virus proliferation. We treated BmN cells with 1,3-di-(N-Carboxybenzoyl-L-leucyl-L-leucyl) amino acetone ((Z-LL)2-ketone), an inhibitor of SPP, and found that the higher the concentration of the inhibitor led to greater inhibition of Bombyx mori nucleopolyhedrovirus (BmNPV) proliferation. To investigate the potential antiviral effects of BmSPP, we down-regulated its expression in BmN cells using knockout vectors and found to affect BmNPV proliferation. We further obtained the BmSPPKO knockout strain using CRISPR/Cas9-based genome editing. The viral DNA content was significantly decreased in BmSPPKO silkworm compared to the control, resulting in an 12.4% lower mortality. These results demonstrated that BmSPP plays a negative regulatory role in silkworm resistance to BmNPV infection and is involved in virus proliferation and replication processes. This suggests that BmSPP acts as the target gene of BmNPV virus resistance in silkworm and can be utilized in resistance breeding programs.